Israel's maritime boundaries - Glassner, Martin Ira; Unger, Michael (Ocean Development and International Law, 1974)
While land boundaries have occupied the attention of Israelis since 1948 and even earlier, they have been little concerned with the sea, and the legislation concerning their maritime boundaries is vague and incomplete. In addition, since the Six Day War Israel occupies territory with several different territorial seas, resulting in a quite complex ad hoc situation. The sea is becoming more important to Israel and she is gradually turning her attention more and more to maritime matters. It would be well if an orderly system of maritime boundaries and cooperation in utilizing the resources of the sea could be arranged with her neighbors, but that seems impossible for the forseeable future. It does seem likely, however, that in connection with or shortly after the forthcoming Law of the Sea Conference, Israel will as a minimum extend her territorial sea from six miles to twelve, while stoutly maintaining the right of free transit through international straits. © 1974 Taylor & Francis Group, LLC.
Keywords: dept.egm

Bedouin of Southern Sinai Under Israeli Administration - Glassner, MI (Geographical Review, 1974)
Keywords: dept.egm

Law of Sea - Research on Maritime Sovereignty and Continental Shelf of Venezuela in Realm of International Law of Sea - Nweihed,kg - Glassner, MI (Annals of the Association of American Geographers, 1974)
Keywords: dept.egm; ⛔ No DOI found

Population Figures for Mandan Indians - Glassner, MI (Indian Historian, 1974)
Keywords: dept.egm; ⛔ No DOI found

Modifying Weather - Social Assessment - Sewell,wrd - Sakalowsky, PP (Professional Geographer, 1974)
Keywords: dept.egm; ⛔ No DOI found

History of Study of Landforms or Development of Geomorphology - .2. Life and Work of Davis,wm - Chorley,rj, Beckinsale,rp and Dunn,a - Martin, GJ (Professional Geographer, 1974)
Keywords: dept.egm; ⛔ No DOI found